Psychosomatic Symptoms and the Organization of Work - Rangel, Fabiana Bittencourt; Godoi, Christiane Kleinübing (Review of Business Management, 2009)
This article has the objective of analyzing the relations between the organization of the work and the manifestation of the psychosomatic symptoms. The method of clinical-qualitative research was used as instrument of data collection, interviews in depth with fourteen individuals of an organization. Initially sought a provisional analytical categorization based on the theoretical framework. After that the interpretations of the statements were organized graphics that highlight the view of the incidence of symptoms and risk factors of work organization that emerged from the discourses. The associated symptoms were headache, stress, physical exhaustion, insomnia, gastritis, depression, anxiety, body aches, and inflammation of the sciatic nerve, distress, lethargy and mood swings. Factors associated with the organization of work have been the work pressure, lack of autonomy, insecurity, a feeling of being undervalued, lack of opportunity, lack of control and excess workload. The qualitative methodology did not attempt to establish a correlation between the two constructs, but the outbreak analyze of the factors that compose them and their possible associations present in the interviews. Key words: Psychosomatic. Work organization. Psychic weight. Symptoms. Work.